1988
DOI: 10.24266/0738-2898-6.2.53
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Quince (Cydonia) Cultivars Using Polyacrylamide Gel Electrophoresis

Abstract: An investigation of available Cydonia (Cydonia oblonga Mill., quince, membrillo) germplasm by isozyme staining of anionic polyacrylamide gradient electrophoresis gels is described. The isozymes of acid phosphatase, esterase, peroxidase and phenol oxidase showed most diversity and usefulness for this purpose. Eleven groups of quince and two groups of x Pyronia (quince-pear crosses) were distinguished by their isozyme patterns. These patterns distinguish between groups of clonal accessions, and the patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, genotypes located closer to the ideal genotype are more desirable than others; thus, genotype Svs1 was more desirable followed by genotypes Nb4, Esf and Et1 while genotypes Nb1, Kvd3 and Svs2 were the most unfavorable and genotype Kvd2 was, of course, the poorest genotype because it was consistently the poorest (Figure 3). Sanchez et al (1988) studied 11 quince genotypes by isozyme patterns which were considered to represent genetic characteristics suitable for identification purposes but the diversity of isozyme patterns was much less than other markers while in the present study using morphologic traits and biplot method could detect the best genotype. The biplot in Figure 4 is used for visualizing the relationships among the genotypes and the lines connecting the biplot origin with the markers for the genotypes are called genotype vectors.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, genotypes located closer to the ideal genotype are more desirable than others; thus, genotype Svs1 was more desirable followed by genotypes Nb4, Esf and Et1 while genotypes Nb1, Kvd3 and Svs2 were the most unfavorable and genotype Kvd2 was, of course, the poorest genotype because it was consistently the poorest (Figure 3). Sanchez et al (1988) studied 11 quince genotypes by isozyme patterns which were considered to represent genetic characteristics suitable for identification purposes but the diversity of isozyme patterns was much less than other markers while in the present study using morphologic traits and biplot method could detect the best genotype. The biplot in Figure 4 is used for visualizing the relationships among the genotypes and the lines connecting the biplot origin with the markers for the genotypes are called genotype vectors.…”
Section: Resultsmentioning
confidence: 81%
“…Probably 'Esme' name may be a mixed population instead of one cultivar. Sanchez et al, (1988) reported that 'Tekes' and 'Limon' cultivars had same isozyme pattern. In our study, this two cultivars were also closely related.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Studies on molecular characterization of quince accessions are limited in the literature (Sanchez, 1988;Yamamoto et al, 2004;Dumanoglu et al, 2009;Bayazit et al, 2011;Azad et al, 2013;Yuksel et al, 2013;Topcu et al, 2015;Pınar et al, 2016). The SSR technique has several advantages, such as high polymorphism, codominance, and reproducibility.…”
Section: Ssr Polymorphismmentioning
confidence: 99%